2007
DOI: 10.1363/3915807
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics Associated with Emergency Contraception Use by Family Planning Patients: A Prospective Cohort Study

Abstract: In addition to discussing and offering advance emergency contraception, providers should further explore specific behaviors and attitudes associated with emergency contraception use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…The data used in the present analysis were collected as part of a five‐year longitudinal study designed to compare the frequency of emergency contraceptive use by women who have advance access with use by women who have only emergency access, and to identify factors associated with acceptance and use of the method 11 . The longitudinal study was approved by the Council’s institutional review board, and this approval was accepted by the affiliated clinics.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The data used in the present analysis were collected as part of a five‐year longitudinal study designed to compare the frequency of emergency contraceptive use by women who have advance access with use by women who have only emergency access, and to identify factors associated with acceptance and use of the method 11 . The longitudinal study was approved by the Council’s institutional review board, and this approval was accepted by the affiliated clinics.…”
Section: Methodsmentioning
confidence: 99%
“…The 26 intake questions were closed‐ended and collected information on demographic characteristics (age, race and ethnicity, marital and partner status, education, occupation and the importance of religion in patients lives), sexual activity, opinions about becoming pregnant in the next year, contraceptive history and emergency contraception (whether the patient had ever used the method, whether staff had discussed and offered it at any previous clinic visit, and whether the patient had accepted it). These variables are defined in detail elsewhere 11 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is suggested that education to students and those in professional practice are both needed to develop healthcare providers prepared to provide thorough and effective contraceptive counseling (Wells et al, 2007). While community knowledge about EC has been targeted and studied in several recent protocols, and it appears that the public's knowledge about EC is improving steadily (Black, Mercer, Kubba, & Wellings, 2008; Gee, Delli‐Bovei, & Chuang, 2007; Whittaker, Berger, Armstrong, Felice, & Adams, 2007), less is known about recent improvements in knowledge and recommendations regarding EC in the population of healthcare providers.…”
mentioning
confidence: 99%